GREEN GROWTH INTERVENTIONS MADE BY GOVERNMENT OF INDIA - Dr. Madhu Thawani (Chelonian Research Foundation, 2023)
Green growth refers to continuous availability of resources, with environment intact along with economic growth and development. Green Growth ensures delivery of natural assets on sustainable basis, makes provision of clean air, water, protecting biodiversity which ensure food production and good health. Natural assets are not infinitely available to us. According to the 2020 Environmental Performance Index, India ranks 169 out of 189 countries. India is emerging as the one of the fastest growing economy in the world. It is the sixth largest economy globally by GDP and the third largest economy in Asia. According to World Bank the Indian economy would grow 8.3% and 7.5% in 2021 and 2022, respectively. To meet its development goals, the Indian economy has to continuously grow which would have huge impact on environment and would also affect the delivery of natural resources which would create roadblocks in growing India economy, as envisaged in EPI report 2020 India ranks in Air Quality (179), Sanitation & Drinking Water (139), Waste Management (103), Biodiversity & Habitat (149), Fisheries (36), and Climate Change (106). The concept of Green Growth spans much beyond climate mitigation and adaptation and aims at achieving economic growth that is socially inclusive and environmentally sustainable. The Ministry of Environment, Forest, and Climate Change recognized green growth in its vision. In this paper we will study the Green Growth interventions made by Government of India. It is a descriptive research and secondary sources would be tapped to collect the data. Keywords: Sustainable Development, Green Growth, Economy, Environment, World Bank, Ministry of Environment, Forest, and Climate Change.